Alternative splicing of RNAs transcribed from the human c-myb gene. - Shen-Ong, G L (1990)
An alternative splicing event in which a portion of the intron bounded by the vE6 and vE7 exons with v-myb homology is included as an additional 363-nucleotide coding exon (termed E6A or coding exon 9A) has been described for normal and tumor murine cells that express myb. We show here that this alternative splicing event is conserved in human c-myb transcripts. In addition, another novel exon (termed E7A or coding exon 10A) is identified in human c-myb mRNAs expressed in normal and tumor cells. Although the myb protein isoform encoded by murine E6A-containing mRNA is larger than the major c-myb protein, the predicted products of both forms of human alternatively spliced myb transcripts are 3'-truncated myb proteins that terminate in the alternative exons. These proteins are predicted to lack the same carboxy-terminal domains as the viral myb proteins encoded by avian myeloblastosis virus and E26 virus. The junction sequences that flank these exons closely resemble the consensus splice donor and splice acceptor sequences, yet the alternative transcripts are less abundant than is the major form of c-myb transcripts. The contribution that alternative splicing events in c-myb expression may make on c-myb function remains to be elucidated.